Eye movement analysis during activities of daily living (ADL) among fully sighted school children - Anis Suzanna Mohamad,; Rifizati Buyong,; Norliza Mohamad Fadzil,; Zainora Mohammed,; Mizhanim Mohamad Shahimin, (Universiti Kebangsaan Malaysia, 2015)
Eye movement is one of the most important mechanisms that function to collect the information from the environment to stimulate the motor action and thus enable a person to perform daily activities. The purpose of this study was to investigate whether eye movement parameters when performing activities of daily living (ADL) is affected by learning effect when the ADL were repeated. Thirteen school children aged between 15 and 19 years old (mean 16.31±1.89 years) participated in this study. They undergone two evaluations, baseline and follow up, separated by at least 10 weeks. The evaluation included assessment of visual acuity at near and distance using Lighthouse reduced ETDRS chart and Early Treatment Diabetic Retinopathy (ETDRS) chart, respectively; eye movement parameters (task duration, saccade latency and number of saccades) while performing ADL (identifying colours, coins and food) were recorded using Positive Science Portable LLC eye tracker. The mean value for the visual acuity at distance and near for baseline and follow up were logMAR -0.05±0.05 and logMAR -0.05±0.05, respectively. The results showed that comparison of eye movement parameters for performance of ADL at baseline and follow up were not statistically significant. Therefore, the findings of this study suggested that learning effect is not a factor that will influence change in eye movement parameters when performing ADL. These findings implied some benefit in using eye movement parameters for example to evaluate performance of ADL when given intervention in persons with nystagmus.